THE EFFECTS OF RAINFALL ON Penaeus monodon Fabricius POPULATIONS IN THE SEGARA ANAKAN LAGOON, CENTRAL JAVA, INDONESIA - Rianta Pratiwi; Sukristiono Sukardjo (BIOTROPIA, 2018)
Segara Anakan Lagoon (SAL) is widely known as a traditional fishing ground for many aquatic organisms and is located in Central Java, an area with high rainfall. The objectives of this study were to determine the effects of rainfall on the distribution of Penaeus monodon Fabricius in SAL and/or mangrove waters, and to explain the cause of yearly fluctuations in fish catch during a 13-year period (1998–2011). The effects of rainfall on the local distribution and abundance of shrimp in SAL, Cilacap, Central Java, Indonesia, were examined using the Anco method for three periods, namely: the first period (commercial catch production, 1998–2011), the second period (December 2010–November 2011), and the third period (December 2011–April 2012), as part of a shrimp fishery and eco-biology study in this region. The marked increase in rainfall from 557 mm during the East Monsoon (June–August) to 1,225 mm in the second transition season (September–November) and West Monsoon (December–February) in the Segara Anakan region enhanced the seasonal movement of shrimp into the Zone IV fishing ground and produced an initial increase in the abundance of adults (CL > 25 mm) from 312 to 2,630 individuals. This initial increase in adult abundance enhanced the shrimp's reproductive potential, while heavy rainfall indirectly supported the recruitment, growth, and survival of juvenile shrimp, increasing the shrimp population in the following year. Lower rainfall from July to September adversely affected the shrimp population and typically resulted in smaller catches (312 individuals). Statistical analysis of the relationship between shrimp catch and annual rainfall showed a high level of significance at 1%.